Mycobacteria - Dobos, Karen M.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Mycobacteria is a comprehensive, peer-reviewed publication focused on advancing mycobacterial research along with their practical applications. Topics covered include: basic and clinical research human and animal research drug discovery antimicrobial resistance treatment schemes biomarkers class descriptions soil and environmental mycobacteriology applications and biotechnology.
Keywords: Medical microbiology; Soil science; Diseases; Immune response; Pathogenic microorganisms; Veterinary medicine; Medical Microbiology; Soil Science; Diseases; Antimicrobial Responses; Veterinary Science